The intercept : a Jeremy Fisk novel - Wolf, Dick. (New York : Harper, 2013)
"An adrenaline-fueled thriller debut in the tradition of Three Days of the Condor from the famed creator of TV's Law & Order, featuring NYPD Special Agent Jeremy Fisk, who is New York City's last hope against an ingenious, multi- pronged terrorist attack"--
Keywords: Police -- New York (State) -- New York -- Fiction; Terrorism -- Prevention -- Fiction; Suspense fiction